Separating adverse-pressure-gradient and Reynolds-number effects in turbulent boundary layers - Sanmiguel Vila, Carlos; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, R. (Physical Review Fluids, 2020)
Zero pressure-gradient (ZPG) turbulent boundary layers (TBLs) at high Reynolds numbers (Re) and TBLs with adverse pressure gradients (APGs) share some similarities such as the emergence of an outer peak in the streamwise variance profile related to the enhancement of large-scale energy. Reynolds-number and pressure-gradient effects tend to cause such an energizing of the outer-layer structures, which makes it difficult to distinguish them, mainly because both effects are usually coupled. Using two experimental data sets of ZPG and APG TBLs in which Re and pressure gradient are analyzed independently, the present paper shows that the two effects have different imprints on the flow. In particular, the analysis shows that (1) the small-scale energy in APG TBLs is, contrary to canonical ZPG TBLs, not universal, but is dependent on the APG strength, (2) the APG enhances both the small- and large-scale energy in the outer region, and (3) the outer-peak location and the amplitude of the streamwise variance scale differently for increasing Re and APG magnitude. These findings may have ramifications on the development of turbulence models since the pressure gradient has a direct influence on the near-wall dynamics.
CRIS-Team Scopus Importer:2023-03-21